Perubahan Kurikulum Pendidikan Agama Islam di Indonesia: Analisis Perubahan dan Tantangan - Andi Alifah Nurul Fathiyah; A'aisyah Ar Rojwah; Qoriina Qoriina; Syarifah Noviyani; Riky Supratama (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: The transformation of the Islamic Education curriculum in Indonesia has been ongoing since the country's independence and continues to evolve in line with social and political dynamics, as well as advances in science and technology. This study aims to analyze the transformation of the Islamic Education curriculum in Indonesia from the 1947 curriculum to the Merdeka curriculum, with a focus on identifying changes in educational approaches and challenges in the implementation process. This study employs a descriptive qualitative approach through literature review and analysis of official documents. The findings trace the dynamics of the paradigm shift in Islamic Religious Education, from an approach based on character and religiosity toward a contextual approach that is adaptive to digital technology and the needs of the times. The results of the study indicate that each curriculum change brings a diverse spirit of renewal. However, each phase of change faces implementation challenges, such as disparities in teacher resources, a lack of contextual pedagogical training, and infrastructure limitations, especially in remote areas. Therefore, this study recommends the need to enhance teacher competencies through continuous training, strengthen regulations for the implementation of adaptive curricula, and foster collaboration among education stakeholders to ensure the success of the Islamic Religious Education curriculum in shaping students' characters to be religious, inclusive, and responsive to the challenges of the times.Abstrak: Transformasi Kurikulum PAI di Indonesia telah berlangsung sejak awal kemerdekaan hingga saat ini, dan terus berkembang mengikuti dinamika sosial, politik, serta kemajuan pada ilmu pengetahuan dan teknologi. Penelitian ini bertujuan untuk menganalisis transformasi kurikulum Pendidikan Agama Islam di Indonesia dari kurikulum 1947 hingga kurikulum Merdeka, dengan fokus pada identifikasi perubahan pendekatan pendidikan serta tantangan dalam proses implementasinya. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui studi pustaka dan analisis dokumen resmi. Temuan menelusuri dinamika pergeseran paradigma Pendidikan Agama Islam, dari pendekatan berbasis karakter dan religiutas menuju pendekatan kontekstual yang adaptif terhadap teknologi digital dan kebutuhan zaman. Hasil penelitian menunjukkan bahwa di setiap perubahan kurikulum membawa semangat pembaruan yang beragam. Namun, setiap fase perubahan dihadapkan pada tantangan implementasi, seperti ketimpangan pada sumber daya guru, minimnya pelatihan pedagogik kontekstual, serta keterbatasan infrastruktur terutama di daerah tertinggal. Oleh karena itu, penelitian ini merekomendasikan perlunya peningkatan kompetensi guru melalui pelatihan berkelanjutan, penguatan regulasi implementasi kurikulum yang adaptif, serta sinergi antar pemangku kepentingan pendidikan, guna memastikan keberhasilan kurikulum PAI dalam membentuk karakter peserta didik yang religius, inklusif, dan responsif dengan tantangan zaman.